Different systems, same inequalities? Post-compulsory education and young adults' literacy in 18 OECD countries - Camilla Borgna (Journal of European Social Policy, 2017)
Education is increasingly seen as a substitute for social policy, but opportunities for skill development vary by social background and educational institutions are not neutral in this respect. While previous research has extensively examined how schooling affects skills distribution, the role of post-compulsory education has been long overlooked. Using data from the 2011/2012 Programme for International Assessment of Adult Competences, this article investigates how selected features of upper secondary and tertiary education are connected to the social stratification of young adults' literacy skills in 18 OECD countries. First, I use individual-level regressions to assess the extent to which disparities in the skills of 24- to 29-year-old individuals are explained by parental education in each country. Second, I apply fuzzy-set qualitative comparative analysis across countries to investigate under which institutional conditions the social stratification of young adults' literacy skills is most severe. The findings point to the existence of functionally equivalent education regimes: young adults face severe disparities not only in socially selective higher education systems but also in relatively open systems characterized by institutional differentiation; moreover, disparities arising during compulsory schooling are consequential for the skill distribution of young adults, underscoring the importance of a life-course approach to education policies.
Keywords: 330; educational inequalities; educational systems; fuzzy sets; higher education; QCA; vocational training